1998
DOI: 10.1149/1.1838590
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Precursor Sites for Pitting Corrosion of Polycrystalline Titanium by Using Different Techniques

Abstract: Scanning electrochemical microscopy (SECM) in ferrocyanide and bromide solutions was used to locate active sites (pitting precursors) on polycrystalline Ti where oxidation of Br and Fe(CN) was possible. Analysis of the electroctrochemically active sites was done by using electron microscopy (SEM), energy dispersive X-ray analysis (EDX), atomic force microscopy (AFM), and in situ confocal laser scanning microscopy (CLSM). Inmost cases, the active sites were found to be associated with particles (inclusions) whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 3 publications
1
56
1
2
Order By: Relevance
“…It complements other scanning probe techniques such as the scanning reference electrode technique (SRET) [178,179], conductive scanning force microcopy (CSFM), electrochemical scanning tunneling microscopy (ECSTM), and scanning Kelvin probe techniques which are popular methods for the investigation of functional materials [180]. Basic experimental approaches include the imaging of the permeability of applied protective coatings [181][182][183][184][185][186][187][188][189][190][191][192][193], the imaging of regions with distinctly higher electron transfer rates which may be precursor sites for pitting corrosion [29,57,[194][195][196][197][198][199][200][201][202][203][204][205][206][207], the initiation of pitting corrosion by local generation of aggressive species at the UME [208,209] and the detection of active corrosion by collecting released species [55,58,60,104,[210][211][212][213][214]…”
Section: Localized Corrosionmentioning
confidence: 99%
“…It complements other scanning probe techniques such as the scanning reference electrode technique (SRET) [178,179], conductive scanning force microcopy (CSFM), electrochemical scanning tunneling microscopy (ECSTM), and scanning Kelvin probe techniques which are popular methods for the investigation of functional materials [180]. Basic experimental approaches include the imaging of the permeability of applied protective coatings [181][182][183][184][185][186][187][188][189][190][191][192][193], the imaging of regions with distinctly higher electron transfer rates which may be precursor sites for pitting corrosion [29,57,[194][195][196][197][198][199][200][201][202][203][204][205][206][207], the initiation of pitting corrosion by local generation of aggressive species at the UME [208,209] and the detection of active corrosion by collecting released species [55,58,60,104,[210][211][212][213][214]…”
Section: Localized Corrosionmentioning
confidence: 99%
“…Fe 2+ , Fe 3+ , H 2 , and O 2 ). Identification of precursor sites for pitting corrosion that often result from local damage of the oxide film has been achieved in the sample generation/tip collection (SG/TC) mode on steel [81][82][83][84][85], Ti [86][87][88][89][90], Ta [91,92], Ni [93], and Al [94,95] by use of their enhanced kinetics of heterogeneous electron transfer to dissolved components. With SECM, identification of those precursor sites in their passive state is possible because of the nondestructive character of the technique.…”
Section: Metalsmentioning
confidence: 99%
“…For a 0.79 cm 2 macroscopic Ti/ TiO 2 electrode it was estimated with the theory of mass transport through individual pores that 69% of the current was passing through eleven precursor regions that comprised only 0.1% of the total area [89]. Basame and White [92] Garfias-Mesias et al [90] concluded inter alia from SECM observation of active regions that precursor sites on Ti can be associated with inclusions of other elements, for example Si and Al. For stainless steel, precursor regions can be associated with MnS inclusions.…”
Section: Metalsmentioning
confidence: 99%
“…SECM imaging experiments can be performed by either feedback or generation-collection (G-C) mode. [6] SECM has been applied successfully to a great variety of corrosion processes including the visualization of anodic and cathodic areas, [7,8] the identification of precursor sites for pitting corrosion, [9][10][11][12] the detection of metastable pit nucleation, [13] the generation of single pits on passive metals, [14][15][16][17][18] the dissolution of inclusions in alloys, [19][20][21] the water uptake and blister formation at organic-coated metals, [22][23][24] the degradation of organic coatings from metal-coating interfaces, [25][26][27][28] the permeation of hydrogen through metals, [29] and the characterization of chemical inertness of ceramic coatings on metals. [30,31] In most instances, the corrosion process is followed through the detection of the metal ion released in the aqueous phase from the corresponding corroding metal or metal alloy.…”
Section: Introductionmentioning
confidence: 99%